2004
DOI: 10.1590/s0102-09352004000100003
|View full text |Cite
|
Sign up to set email alerts
|

Feline immunodeficiency virusinfection: a comparative study of different diagnostic techniques

Abstract: This study evaluated an indirect immunofluorescence assay (IFA) to detect feline immunodeficiency virus infection (FIV) antibody in a comprehensive epidemiological survey of FIV in Argentina. IFA modified in our laboratory, was compared with two other immunoassays, western blot (WB) and a sandwich immunochromatographic commercial kit (SI), and also with a direct polymerase chain reaction (PCR) method that detects proviral DNA. IFA showed to be a test with high sensitivity and specificity, and could be useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Reche et al (1997) and Souza et al (2002) found 8 and 17% of positive cats in Sao Paulo and Rio de Janeiro, respectively (Souza et al, 2002;Reche et al, 1997). The variability of serological and molecular diagnosis of feline immunodeficiency virus infection have been reported lately in others researches, in agreement with our study (Bienzle et al, 2004;Mortola et al, 2004). Seronegative samples with PCR positive results may be also found in cats living in close contact with FIV infected seropositive animals, becoming infected without developing antibodies or disease (Dandekar et al, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Reche et al (1997) and Souza et al (2002) found 8 and 17% of positive cats in Sao Paulo and Rio de Janeiro, respectively (Souza et al, 2002;Reche et al, 1997). The variability of serological and molecular diagnosis of feline immunodeficiency virus infection have been reported lately in others researches, in agreement with our study (Bienzle et al, 2004;Mortola et al, 2004). Seronegative samples with PCR positive results may be also found in cats living in close contact with FIV infected seropositive animals, becoming infected without developing antibodies or disease (Dandekar et al, 1992).…”
Section: Discussionsupporting
confidence: 91%